Motor Impulsivity During Childhood and Adolescence: A Longitudinal Biometric Analysis of the Go/No-Go Task in 9- to 18-Year-Old Twins - Bezdjian, Serena (Dev Psychol, 2014)
In the present study, we investigated genetic and environmental effects on motor impulsivity from childhood to late adolescence using a longitudinal sample of twins from ages 9 to 18 years. Motor impulsivity was assessed using errors of commission (no-go errors) in a visual go/no-go task at 4 time points: ages 9–10, 11–13, 14–15, and 16–18 years. Significant genetic and nonshared environmental effects on motor impulsivity were found at each of the 4 waves of assessment with genetic factors explaining 22%–41% of the variance within each of the 4 waves. Phenotypically, children’s average performance improved across age (i.e., fewer no-go errors during later assessments). Multivariate biometric analyses revealed that common genetic factors influenced 12%–40% of the variance in motor impulsivity across development, whereas nonshared environmental factors common to all time points contributed to 2%–52% of the variance. Nonshared environmental influences specific to each time point also significantly influenced motor impulsivity. Overall, results demonstrated that although genetic factors were critical to motor impulsivity across development, both common and specific nonshared environmental factors played a strong role in the development of motor impulsivity across age.